2019
DOI: 10.3847/1538-4357/ab4795
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Cooling as a Result of Mixing by the Nonlinear Kelvin–Helmholtz Instability

Abstract: Recent observations show cool, oscillating prominence threads fading when observed in cool spectral lines and appearing in warm spectral lines. A proposed mechanism to explain the observed temperature evolution is that the threads were heated by turbulence driven by the Kelvin-Helmholtz instability that developed as a result of wave-driven shear flows on the surface of the thread. As the Kelvin-Helmholtz instability is an instability that works to mix the two fluids either side of the velocity shear layer, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…The evolution of the loop profile is characterized by fitting the transverse density profile with a model based on a circular cross-section and linear density profile in the inhomogeneous layer, which is satisfied exactly for the initial condition but otherwise an approximation. They therefore correspond to a value which is averaged in the azimuthal direction, whereas it is known from previous work (e.g., Barbulescu et al, 2019;Hillier and Arregui, 2019) and our Figure 1 that KHI causes density perturbations to develop which exhibit the same m = 1 symmetry as the kink mode. For example, the loop becomes extended in the direction of its displacement (e.g., Karampelas and Van Doorsselaere, 2018).…”
Section: Numerical Simulation Of Non-linear Evolutionmentioning
confidence: 57%
“…The evolution of the loop profile is characterized by fitting the transverse density profile with a model based on a circular cross-section and linear density profile in the inhomogeneous layer, which is satisfied exactly for the initial condition but otherwise an approximation. They therefore correspond to a value which is averaged in the azimuthal direction, whereas it is known from previous work (e.g., Barbulescu et al, 2019;Hillier and Arregui, 2019) and our Figure 1 that KHI causes density perturbations to develop which exhibit the same m = 1 symmetry as the kink mode. For example, the loop becomes extended in the direction of its displacement (e.g., Karampelas and Van Doorsselaere, 2018).…”
Section: Numerical Simulation Of Non-linear Evolutionmentioning
confidence: 57%
“…Nonetheless, "low height" is only a conjecture because we assume that the TR is under the corona. In reality, TR could just come from the outer part of a feature (like a jet) that is cooler inside, as in Hillier & Arregui (2019).…”
Section: Synthetic O V/vi and Si IV Emissionsmentioning
confidence: 99%
“…Not only is this initial energy unable to provide substantial heating, ref. [95] showed that if the instability forms at the boundary of a prominence, the mixing of cold, dense plasma with much hotter and more tenuous coronal plasma can cause an increase in the radiative losses and, thus, lead to enhanced cooling. This increase in the energy loss rate is much larger than the energy dissipation that could be obtained due to the relatively low wave energy content.…”
Section: Wave Excitationmentioning
confidence: 99%
“…At the time, this was posited as evidence for wave heating in action. However, a later study by [95] argued this was not a result of energy dissipation, but was instead caused by the mixing of hot coronal plasma with a cooler prominence material. This leads to an average temperature increase in the prominence boundary, causing the transfer of emission from cooler to hotter lines.…”
Section: Observational Considerationsmentioning
confidence: 99%